SELECTED BIOMARKERS IN SEPSIS: IL-6, sTREM-1 AND NEUTROPHIL CD64 - A LITERATURE REVIEW - Midera, Aleksander; Popielarska, Kinga; Niwińska, Klaudia Elżbieta; Leśniak, Natalia Maria; Zakrzewska, Anna Maria; Leśniak, Julia Aleksandra; Borowski, Michał; Michalak, Julia Agnieszka; Augustyn, Monika (International Journal of Innovative Technologies in Social Science, 2026)
Background: Sepsis is a life-threatening condition characterised by organ dysfunction caused by a dysregulated host response to infection and remains a major cause of morbidity and mortality worldwide. Early recognition is clinically challenging because initial symptoms are non-specific and commonly used inflammatory markers have limited diagnostic performance. Consequently, there is ongoing interest in biomarkers that enable faster and more accurate identification of sepsis.Aim: To discuss selected sepsis biomarkers: interleukin-6 (IL-6), soluble TREM-1 (sTREM-1), and neutrophil CD64 expression, with particular emphasis on biological mechanisms, clinical utility, and diagnostic limitations.Materials and methods: A narrative review of the literature was undertaken. Publications from 2016 to 2025 indexed in PubMed/MEDLINE, Scopus, and Google Scholar were analysed, including clinical studies, reviews, and meta-analyses. Evidence was assessed with respect to biological mechanisms, diagnostic and prognostic performance, and limitations of the biomarkers.Results: Neutrophil CD64 expression shows high specificity for bacterial infection and sepsis; however, routine use is constrained by limited assay standardisation and the absence of validated cut-off values. IL-6 rises very early and has prognostic value, correlating with the severity of organ dysfunction and mortality risk, but it has low specificity. sTREM-1 reflects activation of the TREM-1 axis and the intensity of the inflammatory response; however, its ability to distinguish sepsis from non-infectious SIRS is limited.Conclusions: None of the reviewed biomarkers should be used as a stand-alone diagnostic test. The greatest clinical value is likely to be achieved with a multiparametric approach that combines clinical assessment and organ dysfunction scores with biomarkers representing different stages of the immune response. This strategy may improve early recognition, risk stratification, and monitoring of sepsis.